Optimalisasi Partisipasi Masyarakat dalam Kegiatan Kebersihan untuk Menciptakan Lingkungan Sehat dan Berkelanjutan - Didit Darmawan; Putri Syafa Az-Zahra; Rahayu Mardikaningsih; Mila Hariani; Fayola Issalillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Optimizing community participation in cleaning activities is an important step to create a healthy, comfortable, and sustainable environment. This research aims to understand how communities engage in cleanliness activities, the factors that affect their level of involvement, as well as the strategies that can be applied to improve the effectiveness of community-based cleanliness programs. This study was conducted through literature studies from various journals and previous research that discussed community empowerment, environmental care behavior, and waste management. The results of the analysis showed that community participation was influenced by environmental awareness, local support and leadership, quality of communication between residents, availability of supporting facilities, and consistency of program implementation. In addition, collaboration between local governments, educational institutions, and local communities also strengthens the success of cleaning activities. These findings emphasize the importance of careful planning, clear division of roles, and the implementation of an asset-based community approach to Asset-Based Community Development (ABCD) to encourage active engagement and sustainability of environmental programs.